Occupational risks existing in mobile pre-hospital care: Integrative review (Revista Contexto & Saúde, 2023)
The present study aims to identify as scientific evidence on the treatment of risks of mobile pre-hospital care (PHC). This is a research, bibliographic LI, of the integrative type, developed in the databases Latin American and Caribbean Literature in Health Sciences, SciVerse Scopus (SCOPUS) and PubMed based on the following review question: “What are the scientific facts about of knowledge risks in mobile hospital care workers?” There were 1752 studies, 38 of which were selected for review. The results address the risk factors related to the development of diseases at work in mobile APH, namely: exposure to infectious agents, traffic accidents, excessive weight lifting and urban violence. Subsequently, the risk factors, stress, psychosocial burnout by the mobile worker. Mobile workers are daily exposed to risks of reception, whether triggered by biological, physical or mental affective factors or by the specificity of their work context.